On Weyl Multipliers of Almost Everywhere Unconditional Convergence of Series With Respect to General Haar and Franklin Systems - Barkhudaryan, Rafayel; Gevorkyan, Gegham (Armenian Journal of Mathematics, 2026)
We obtain necessary and sufficient conditions for an increasing nonnegative sequence $ω_n$, $n\in\mathbb{N}$, to be a Weyl multiplier for a.e. unconditional convergence for general Haar or Franklin systems corresponding to an admissible sequence ${\cal T}$.
Keywords: General Haar System; General Franklin System; Almost Everywhere Unconditional Convergence; Weyl Multipliers